ANALISIS SENTIMEN OPINI PENGGUNA TWITTER PADA APLIKASI BIBIT MENGGUNAKAN MULTINOMIAL NAÏVE BAYES - Zelin Gaa Ngilo; Nuryuliani Nuryuliani (Asosiasi Dosen Muda Indonesia, 2023)
The COVID-19 pandemic has increased the interest number of capital market investors in Indonesia. One of the factor in Indonesian’s investment interest is the emergence of fintech in the investment sector. One of the fintech companies in mutual fund investment is